Real Hypersurfaces in a Complex Projective Space with Umbilic Points - S.H, Kon,; T.H, Loo, (Malaysian Journal of Science, 2007)
It is well known that there exists no totally umbilical real hypersurfaces M in a non-flat complex space form. Due to this fact, Niegerball and Ryan asked if there is any real hypersurface in a non-flat complex space form with umbilic points. In this paper, we shall answer this question in the affirmative by giving an example in complex projective space.